A Simulation of the Extended States of Fiber Bundle in a Roller-drafting Process (Journal of Fiber Bioengineering and Informatics, 2018)
Many studies indicate that the irregularity of the bundle of output sliver was caused by the irregularaction of the fibers in the drafting zone. In this research, each staple fiber length of the bundle inthe back roll nip and the accelerated points of every fiber in this bundle were generated by usingMonte Carlo method according to the theories of the density function of the length distribution usingnonparametric kernel estimation method and parabolic-type probabilistic density function of acceleratedpoints distribution. The profile changes of the fiber number in cross section of the bundle in drawingprocess was simulated, and the various states of the bundle and the attenuation curve of bundle in thedrafting zone were obtained. The profiles of the state curves of the bundle changes shows a turning areaobviously and the profiles of the attenuation curve experienced a jerk near the front roll, which causedirregularities in the linear density of the output sliver.